SMMS: document management in agile model for software maintenance - Abdul Samat, Pathiah; Mohamed Nawi, Mohamed Zulkifli (Science and Engineering Research Support Society, 2019)
Study shows that most challenging task in software development life cycle is software maintenance,because all of changes made must documented for future used. Thus, an efficient and newest documentation is vital in software maintenance to ensure its activities will not jeopardized. However, this is not as we thought. The popular models such as agile development has ruined the importance of maintenance tasks in software development life cycle. The agile models focused only on verbal communication within development team to provide faster development where the information of the product and its features exists within the heads of the developers but any changes will not documented in a design document. Therefore, the major problem of Agile models is the absence of latest documentation and this issue supposed not exist in software maintenance which is depend on previous documentation. Thus, our aim is to add document management in agile model for software maintenance processes. The result shows that our concept is successful and useful for software maintenance.